TRAINING AND SUPPORT FOR A PERSON-CENTRED APPROACH TO SUPPORTING FAMILY CARERS: A FUTURE DIRECTION TO ACHIEVE IMPROVED OUTCOMES IN PALLIATIVE AND END OF LIFE CARE. Issue 1 (1st March 2015) - Ewing, G; Diffin, J; Austin, L; Grande, G
Abstract : Introduction: In palliative care a key policy driver is carer assessment and support. For provider services to achieve meaningful change in carer outcomes in the future requires a change to a person-centred approach for supporting family carers. The Carer Support Needs Assessment Tool (CSNAT) intervention facilitates a person-centred assessment and support process that is carer-led. Targeted practitioner training and support is required as this represents a change from current practitioner-led approaches. Aim(s) and method(s): To test and revise a training and support package for implementation of carer-led assessment and support in palliative care practice, informed by the Promoting Action on Research Implementation in Health Services (PARiHS) Framework. 36 palliative care services participated including specialist community teams, hospice at home and social work/family support teams. The researchers delivered one day training on carer-led assessment and support: reflection on existing approaches; background to the CSNAT; interactive sessions on integrating CSNAT in practice. 2–3 practitioner 'champions' per site attended (N=82) then cascaded training and facilitated implementation within sites. Peer support was through Skype/Webex discussion sessions. The PARiHS Framework informed champion interview analysis. Results: The finalised training and support package addresses: (1) nature of the evidence – underpinning policy/research, CSNAT approach and its benefits; (2) organisational context—recommended internal managerial, administrative, and IT support (3) internal facilitation including resources for champions to cascade training (4) external facilitation by the research team – Webex support networks/information exchange. Conclusions: The package provides a changed approach to carer support provision for future palliative care practice with potential to improve carer outcomes.